Cinquante ans depuis la révolution des œillets - Lincoln Secco; Osvaldo Coggiola (Cahiers d’histoire.)
The Carnation Revolution was Portuguese and European. The issues that drove it were common to post-war European societies: decolonization, political democracy (fight against authoritarianism and dictatorships), intensification of class clashes. In Portugal, these problems were concentrated and exploded in a short space of time, thanks to a major crisis in the Armed Forces. Its political actors, from the MFA to the extreme left, were forced to improvise political responses to events that often overtook them. In Europe and around the world, it was seen as a continuation of the wave that began in 1968, both in the East and in the West. Its outcome involved all international political forces, including the USA and international left currents. The article seeks to give a synthetic account of the complex panorama that marked a process that, together with the end of the “dictatorship of the colonels” in Greece and Spanish democratization, conditioned two of the great milestones of the last quarter of the 20th century: the emergence of the European Union and the neoliberal wave.